ATP-P2X7R pathway activation limits the Tfh cell compartment during pediatric RSV infection - Russo, Constanza; Raiden, Silvina; Algieri, Silvia; Bruera, María José; De Carli, Norberto; Sarli, Mariam; Cairoli, Héctor; De Lillo, Leonardo; Morales, Ivanna; Seery, Vanesa; Otero, Adrián; Sananez, Inés; et al. (Frontiers in Immunology, 2024)
Background Follicular helper T cells (Tfh) are pivotal in B cell responses. Activation of the purinergic receptor P2X7 on Tfh cells regulates their activity. We investigated the ATP-P2X7R axis in circulating Tfh (cTfh) cells during Respiratory Syncytial Virus (RSV) infection. Methods We analyzed two cohorts: children with RSV infection (moderate, n=30; severe, n=21) and healthy children (n=23). We utilized ELISA to quantify the levels of PreF RSV protein-specific IgG antibodies, IL-21 cytokine, and soluble P2X7R (sP2X7R) in both plasma and nasopharyngeal aspirates (NPA). Additionally, luminometry was employed to determine ATP levels in plasma, NPA and supernatant culture. The frequency of cTfh cells, P2X7R expression, and plasmablasts were assessed by flow cytometry. To evaluate apoptosis, proliferation, and IL-21 production by cTfh cells, we cultured PBMCs in the presence of Bz-ATP and/or P2X7R antagonist (KN-62) and a flow cytometry analysis was performed. Results In children with severe RSV disease, we observed diminished titers of neutralizing anti-PreF IgG antibodies. Additionally, severe infections, compared to moderate cases, were associated with fewer cTfh cells and reduced plasma levels of IL-21. Our investigation revealed dysregulation in the ATP-P2X7R pathway during RSV infection. This was characterized by elevated ATP levels in both plasma and NPA samples, increased expression of P2X7R on cTfh cells, lower levels of sP2X7R, and heightened ATP release from PBMCs upon stimulation, particularly evident in severe cases. Importantly, ATP exposure decreased cTfh proliferative response and IL-21 production, while promoting their apoptosis. The P2X7R antagonist KN-62 mitigated these effects. Furthermore, disease severity positively correlated with ATP levels in plasma and NPA samples and inversely correlated with cTfh frequency. Conclusion Our findings indicate that activation of the ATP-P2X7R pathway during RSV infection may contribute to limiting the cTfh cell compartment by promoting cell death and dysfunction, ultimately leading to increased disease severity.